Case report: Tisagenlecleucel for treatment of relapsed B- acute lymphoblastic leukemia in a patient with CHEK2 mutation - Ipe, Abraham; Angiolillo, Anne; Jacobsohn, David; Cheng, Jinjun; Bornhorst, Miriam; Turner, Joyce; Vatsayan, Anant (Frontiers in Pediatrics, 2023)
Background: Germline Checkpoint Kinase 2 gene (CHEK2) mutations can increase the risk of solid tumors. Recently, they have been identified as risk factors for hematologic malignancies. However, to the best of our knowledge, B-acute lymphoblastic leukemia (B-ALL) has never been described as a presenting manifestation of germline CHEK2 mutation. Chimeric antigen receptor-T (CAR-T) cell therapy directed against CD19 antigen (tisagenlecleucel) is a novel cellular therapy for treatment of relapsed/refractory (R/R) B-ALL. The use of tisagenlecleucel has not been described in patients with CHEK2 mutations. Case Presentation: We describe a case of a pediatric patient with a heterozygous CHEK2 mutation (c.1100delC (p. Thr367Merts*15) successfully treated with tisagenlecleucel for relapsed B-ALL to avoid hematopoietic cell transplant (HCT). The twelve-year-old boy was diagnosed with National Cancer Institute (NCI) high-risk B-ALL (white blood cell count >50,000/mcL), with no extramedullary disease. Cytogenetic analysis revealed normal karyotype but fluorescent in situ hybridization (FISH) showed 93% positivity for CRLF2/P2RY8 rearrangement. He was treated as per Children’s Oncology Group (COG) AALL1131 therapy and achieved a complete remission. Seven months after diagnosis, he was found to have papillary thyroid carcinoma with no evidence of metastatic disease. The patient underwent a total thyroidectomy with central lymph node biopsy and radioactive iodine therapy. His biological mother and fraternal twin brother carried the same germline CHEK2 mutation with no history of malignancy. The biological father tested negative for the familial mutation. Genetic panel also identified three variants of unclear significance: CDKN2A (c.370C>T; p. Arg124Cys), FLCN (c.62G>A (p. Cys21Tyr) and SDHAF2 (c.139A>G (p. Met47Val). Extended family history also revealed a diagnosis of leukemia in maternal uncle at the age of 44 years. Fifteen months after diagnosis the patient had a relapse of B-ALL (both medullary and extramedullary with blasts in CSF), which was successfully treated with tisagenlecleucel. The patient remains in remission 3 years after receiving tisagenlecleucel. Conclusion: As conventional chemotherapy and radiation can potentially increase the risk of DNA damage and development of secondary malignancies, CD19 CAR-T therapy (tisagenlecleucel) can be used as a substitute for intensive re-induction chemotherapy and HCT in patients with a germline CHEK2 mutation.